Joule heating of carbon pixels for on-demand thermal patterning. (15th April 2021) - Anas, Muhammad; Mustafa, Mazin M.; Carey, Daniel G.; Sarmah, Anubhav; LeMonte, Joshua J.; Green, Micah J.
Abstract: Here we report the Joule heating of graphite-based pixel arrays using direct current (DC) power and alternating current (AC) power. We show performance of a DC applicator for scalable heating and thermal pattern generation. We demonstrate, for the first time, large-area non-contact heating using microstrip patch antennas operating at 2.45 GHz. We find that the steady-state temperature correlates with the surface conductivity of the individual pixel, and there is an optimum conductivity of the pixel associated with efficient heating in both DC and AC applicators. The applicators developed in this study allow for thermal gradients and patterns by tuning the conductivity of each individual pixel and can be used with any type of carbon-based material such as carbon nanotubes and laser-induced graphene. The applicators could be extended to use for thermal displays, deicing and defrosting, and localized curing of composites. We also demonstrate Joule heating as a useful metric for damage sensing in conductive coatings. Graphical abstract: Image 1